Biochemical study of glutathione reductase (GSH-Red) in Tissue Homogenate of Breast Tumors - Baghdad Science Journal (مجلة بغداد للعلوم)
Breast tumor patients generally have more oxidative stress than normal females. This was clear from significant decrease (P